Analisis Yuridis Implementasi Tugas dan Kewenangan Notaris dalam Praktik Kenotariatan ( Kantor Notaris Sahrul, S.H., M.Kn.) - Zuhdi Hasibuan; Siti Marwah; Ahmad Sulaiman; Chandra Ali Hanafiah; Rizki Afwina Seruni Dewi; Muslim Hasan; Akmal Fadli; Sarah Sarah (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the implementation of notary duties and authorities in notarial practice and the contribution of internship activities to improving student competency. Notaries as public officials have attribution authority based on Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary. This study uses a normative-empirical legal research method with a statutory regulatory approach and a field practice approach through internship activities at the Notary Office of Sahrul, S.H., M.Kn. Data were obtained through direct observation, documentation studies, and literature studies sourced from notarial journals and theses. The results of the study indicate that the implementation of notary duties and authorities has been carried out in accordance with the provisions of laws and regulations, especially regarding the procedures for making authentic deeds as regulated in Article 1868 of the Civil Code. In addition, the internship activities provide practical experience regarding the application of the principles of legal certainty, prudence, and professional responsibility of notaries. Thus, there is a match between notarial legal theory and empirical practice in the field.